THE FIRST OUTBREAK OF VIRAL ENCEPHALOPATHY AND RETINOPATHY IN FARMED SEA BASS (Dicentrarchus labrax) IN SLOVENIA - Rosvita Sitar (Slovenian Veterinary Research, 2021)
Abstract: Viral encephalopathy and retinopathy (VER) is considered a serious disease of several marine fish species, caused by RNA virus belonging to the family Nodaviridae, genus Betanodavirus. The disease is spread almost worldwide and causes significant losses among diseased fish. It is characterised by vacuolation of the central nervous system and the retina. In July 2018, behavioural abnormalities i.e. altered swimming, swirling and vertical floating as well as lethargy and anorexia were observed in farmed sea bass (Dicentrarchus labrax) in the Gulf of Piran (Slovenia), associated with significant mortality. The disease initially occurred in juvenile sea bass, but later market-sized fish also became affected. Diseased fish displayed ocular opacity and multifocal skin ulceration on the head. Emaciation in some fish was also evident. Histopathology revealed characteristic vacuolation in the brain and retina. Performing a RT-PCR and RT-qPCR techniques, we have identified and confirmed the presence of betanodavirus nucleic acid in ocular and brain tissues. In addition, concentrations of the causative agent of VER in spleen and kidney did result in significantly higher viral yield than expected. Phylogenetic analysis showed that Slovenian isolate belongs to RGNNV species of betanodaviruses. Based on the clinical signs, gross and typical microscopic lesions and results of molecular analyses, we can conclude that farmed sea bass from the Gulf of Piran were affected with VER. To the best of our knowledge, this is the first report of VER in Slovenia. Key words: viral encephalopathy and retinopathy; betanodavirus; sea bass; histopathology; RT-qPCR